10. RESULTS OF SURGICAL TREATMENT OF THORACOLUMBAR SPINE FRACTURE WITH PERCUTANEOUS PEDICLE SCREW FIXATION (Vietnam Journal of Community Medicine, 2024)
Introduction: Thoracic-lumbar spine injuries are a common clinical situation and can leave serious sequelae if not treated promptly. Surgery is indicated when the patient has mechanical and neurological instability. Open surgery requires a long incision, dissection of a lot of soft tissue causing blood loss, a lot of pain after surgery, a long hospital stay, and in some cases back muscle atrophy causing lasting back pain.Objective: Evaluate treatment results and determine the complication rate of thoracolumbar spine fracture surgery with percutaneous pedicle screw fixation.Research methods:Prospective cross-sectional description of 30 patients with unstable thoracolumbar spine fractures, Frankell E.Results: 30 patients (21 men, 9 women); Average age 42±12 (range 22-65 years old); Mechanism of injury from traffic accidents 76.7%, high falls 23.3%; Clinical symptoms of back pain 100%; The most common lesion location was D12-L1, accounting for 90%; Characteristics of fractures on CT: Compression fractures: 20%; Fracture: 63.3%; Belt fracture: 3.3%; Dislocated fractures: 13.3%; The rate of screwing into the bow leg was 100%; Surgical infection rate 0%; Recovery results according to Hirabayashi formula after 3 months: good: 50%; very good: 50%; average or bad: 0%.Conclusion: Surgery for thoracolumbar spine fractures with percutaneous pedicle screw fixation is a safe surgery, providing good postoperative results and high recovery rate.
Keywords: Thoracic-lumbar spine fracture, percutaneous pedicle screw fixation.